The Punjab Preservation of Subsoil Water Act: a regulatory mechanism for saving groundwater - Sharma, Bharat R.; Ambili, G.K.; Sidhu, B.S. (2010)
Groundwater resources, believed to have played an important role in Green Revolution induced agricultural productivity rise in India, is under serious threat due to overdraft. The unregulated exploitation of this limited resource had brought Indian Punjab into a state of acute water crisis. Homogenized cropping followed in the state, with water guzzling rice being the highly favoured crop in kharif, is the most to blame for this resource crisis. The plunging water levels in the state led the state Government to regulate groundwater use byseveral district and indirect measures. The Punjab Preservation of Sub-soil Water Act-2009 is such an effort to conserve groundwater resource by mandatory delay in the transplanting paddy beyond 10th June to escape periods of very evapotranspiration demands. The present paper investigates the potential of the act in bringing about anticipated real water savings of groundwater. It also looks at the impact of this regulatory framework on savings in agricultural electricity consumption in the state.